Vienna Still a Just City? - Kazepov, Yuri; Verwiebe, Roland (Built Environment City Studies, 2022)
This book explores and debates the urban transformations that have taken place in Vienna over the past 30 years and their consequences in policy fields such as labour and housing, political and social participation and the environment. Historically, European cities have been characterised by a strong association between social cohesion, quality of life, economic ambition and a robust State. Vienna is an excellent example for that. In more recent years, however, cities were pressured to change policy principles and mechanisms in the context of demographic shifts, post-industrial transformations and welfare recalibration which have led to worsened social conditions in many cities. Each chapter in this volume discusses Vienna's responses to these pressures in key policy arenas, looking at outcomes from the context-specific local arrangements. Against a theoretical framework debating the European city as a model of inclusion and social justice, authors explore the local capacity to innovate urban policies and to address new social risks, while paying attention to potential trade-offs. The book questions and assesses the city's resilience using time series and an institutional analysis of four key dimensions that characterise the European city model within the context of post-industrial transition: redistribution, recognition, representation and sustainability. It offers a multiscalar perspective of urban governance through labour, housing, participatory and environmental policies, bringing together different levels and public policy types. Vienna: Still a Just City? is aimed at academics, researchers and policy-makers in urban studies, including urban sociology, ecology, geography and welfare.